The efficacy of endoscopic ultrasonography in local staging of rectal tumors - Belkıs Ünsal,; Emrah Alper,; Behlül BAYDAR,; Mahmut Arabul,; Fatih Aslan,; Mustafa Çelik,; Zafer BUYRAÇ,; Serdar AKÇA, (Turkish Journal of Gastroenterology, 2019)
-